Intussusceptive angiogenesis-on-a-chip: Evidence for transluminal vascular bridging by endothelial delamination - Sabrina C. R. Staples; Hao Yin; Frances S. K. Sutherland; Emma K. Prescott; Dylan Tinney; Douglas W. Hamilton; Daniel Goldman; Tamie L. Poepping; Christopher G. Ellis; J. Geoffrey Pickering (Proceedings of the National Academy of Sciences, 2025)
Intussusceptive angiogenesis is an increasingly recognized vessel duplication process that generates and reshapes microvascular beds. However, the mechanism by which a vessel splits into two is poorly understood. Particularly vexing is formation of the hallmark transluminal endothelial cell bridge. How an endothelial cell comes to cross a flowing lumen rather than line it is enigmatic. To elucidate this, we used a microvessel-on-a-chip strategy, creating a microconduit coherently lined with flow-sensitive endothelial cells but in which transluminal bridges also formed. Bridge morphologies ranged from filamentous strand to multicellular columns with a central extracellular matrix-containing core. These bridge architectures were found to recapitulate those in microvessels in embryos, tumors, diseased organs, and the dermis of patients with limb-threatening ischemia. Time-lapse, multiplane, three-dimensional (3D) microscopy of the microphysiologic conduit revealed that bridges arose from endothelial cells oriented orthogonal to flow that partially released from the wall while retaining attachments at the ends. This delamination process was blocked by hyperactivation of Rho and augmented by interventions that weaken cell–substrate interactions, including inhibiting nonmuscle myosin II and blocking α5ß1 integrin. Thus, endothelial cells can leave their monolayer and transect a flowing lumen through controlled delamination. This previously unrecognized lumen entry program could explain the launch of intussusceptive angiogenesis and opens a framework for intervening.